Exhibit of gold bars and nuggets, Alaska Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: One and a Quarter Million. Printed on verso: 91. One and a Quarter Million. Upon a stand within a glass case, within an iron cage, within a classic temple, within the Alaska Building; so secure and yet so easily seen, repose bars and nuggets of pure gold valued at a million and a quarter dollars. 1909. The Alaska-Yukon-Pacific Exposition. Official Photograph. Published by Robert A. Reid. 488 Arcade. Made in Seattle. PH Coll 777 Reid.91 (See also PH Coll 78.118) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number